Situational Syllabus in Vocabulary English for Nursing Book: Occupational Purposes - Maryani, Maryani; Arroyyani, Risa (Acitya: Journal of Teaching and Education, 2024)
This aims to design a syllabus for "Vocabulary English for Nursing" book for occupational purposes with a specific focus on enhancing vocabulary acquisition, speaking proficiency, and pronunciation skills. This study utilizes ADDIE primarily focusing on the Analysis and Design stages. The syllabus results in ten units, each unit was designed to foster dialogue practices, simple expressions, and vocabulary enrichment. The learning competencies integrated into this syllabus align with the Independent User B1 of CEFR (Common European Framework of Reference for Languages: Learning, Teaching, Assessment. The outcome of this study includes a designed syllabus for "Vocabulary English for Nursing" book and the organization of the book. Future research will cover the further stages.